Numerical Investigation into the Gas Production from Hydrate Deposit under Various Thermal Stimulation Modes in a Multi-Well System in Qilian Mountain - Bo Li; Yuan Ye; Tingting Zhang; Qingcui Wan (Entropy, 2021)
The primary objective of this study was to investigate the energy recovery performance of the permafrost hydrate deposit in the Qilian Mountain at site DK-2 using depressurization combined with thermal injection by the approach of numerical simulation. A novel multi-well system with five horizontal wells was applied for large-scale hydrate mining. The external heat is provided by means of water injection, wellbore heating, or the combinations of them through the central horizontal well, while the fluids are extracted outside from the other four production wells under constant depressurization conditions. The injected water can carry the heat into the hydrate deposit with a faster rate by thermal convection regime, while it also raises the local pressure obviously, which results in a strong prohibition effect on hydrate decomposition in the region close to the central well. The water production rate is always controllable when using the multi-well system. No gas seepage is observed in the reservoir due to the resistance of the undissociated hydrate. Compared with hot water injection, the electric heating combined with normal temperature water flooding basically shows the same promotion effect on gas recovery. Although the hydrate regeneration is more severe in the case of pure electric heating, the external heat can be more efficiently assimilated by gas hydrate, and the efficiency of gas production is best compared with the cases involving water injection. Thus, pure wellbore heating without water injection would be more suitable for hydrate development in deposits characterized by low-permeability conditions.